2022
DOI: 10.1007/s10212-022-00600-5
|View full text |Cite
|
Sign up to set email alerts
|

Persisting in Physics and the Physics Olympiad — Impact of Gender Identification and Sense of Belonging on Expectancy-Value Outcomes

Abstract: The German Physics Olympiad is an extracurricular science contest for students. Here, they have the opportunity to compete against other talented students, can do physics outside of school, and take a first step to more engagement in the domain. Yet, female students participate in the competition in fewer numbers and are disproportionally more likely to drop out of the contest earlier than the male students.The present study hence explored the question to which extent the German Physics Olympiad provides a thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…The value that students assign to their academic tasks and disciplines affects their attachment to learning activities and environments via motivation. Regarding the link between belonging and valuing, a study of high school students in Germany found that a more heightened sense of belonging positively affected students' expectations for success within the expectancy-value framework (Ladewig et al, 2022). A study of middle school students found significant correlations between belonging and value (Goodenow, 1993).…”
Section: Major Valuingmentioning
confidence: 99%
“…The value that students assign to their academic tasks and disciplines affects their attachment to learning activities and environments via motivation. Regarding the link between belonging and valuing, a study of high school students in Germany found that a more heightened sense of belonging positively affected students' expectations for success within the expectancy-value framework (Ladewig et al, 2022). A study of middle school students found significant correlations between belonging and value (Goodenow, 1993).…”
Section: Major Valuingmentioning
confidence: 99%
“…Specifically, FGCS would report lower expectancyvalue motivation and engagement than CGCS if they experienced cultural mismatch. Finally, psychological factors, including sense of belonging (Gopalan and Brady, 2020;Ladewig et al, 2022) and stress (Simons and Steele, 2020), are predictors of motivation and engagement, suggesting that FGCS would be at most risk of experiencing lower expectancy-value motivation and engagement for school compared to CGCS.…”
Section: Contextualizing Differences By Generation Statusmentioning
confidence: 99%
“…The study presented in this paper was part of the larger project "Identiphy -Identity development in physics!" (see also Ladewig et al, 2022). The project included a longitudinal study with two cohorts of German Physics Olympiad participants.…”
Section: Project "Identiphy -Identity Development In Physics!"mentioning
confidence: 99%